Preschool Teachers' Cognitions, Emotions, and Tolerance toward Children's Hypothetical Social Behaviors in the Classroom - Maryse Guedes; Manuela Veríssimo; António J. Santos (MDPI AG, 2023)
Teachers' tolerance toward children's social behaviors is, in part, guided by teachers' cognitions and emotions. Few studies have examined the associations between teachers' cognitions, emotions, and tolerance toward children's social behaviors. This study aimed to (1) describe the cognitions, emotions, and tolerance of Portuguese preschool teachers toward children's shy, physically and relationally aggressive, rough-and-tumble play, exuberant, and unsociable behaviors at preschool, depending on children's sex; and (2) examine the direct and indirect associations (via teachers' emotions) between teachers' cognitions and tolerance toward children's social behaviors, depending on children's sex. One hundred and seven preschool teachers completed the Child Behaviors Vignettes. Preschool teachers displayed more negative views toward children's physical and relational aggression, reported positive perspectives toward children's rough play and mixed attitudes toward children's exuberance, and differentiated shy from unsociable behaviors. Direct associations between teachers' cognitions and tolerance were found only for physical aggression. Teachers' anticipation of negative peer costs and academic performance appear to exert an indirect influence on teachers' tolerance toward physical aggression and unsociability, via increased levels of worry. These findings highlight the role of teachers' emotions for tolerance toward children's social behaviors and the need to enhance their self-awareness.